GPs’ experiences of diagnosing and managing childhood eczema: a qualitative study in primary care - Le Roux, Emma (Br J Gen Pract, 2018)
BACKGROUND: Eczema is common among children, and in the UK the majority are managed by GPs. The most common cause of poor disease control is incorrect use of topical treatments. There is a lack of research into the challenges faced by GPs in diagnosing and managing this condition. AIM: To explore the experiences of GPs in assessing and managing children with eczema. DESIGN AND SETTING: Qualitative study in primary care in England. METHOD: Semi-structured interviews with 15 GPs were audiorecorded, transcribed verbatim, and analysed thematically using the framework method. RESULTS: GPs described a paucity of dermatology training. Although most GPs were confident diagnosing uncomplicated eczema, they reported using a trial-and-error approach to prescribing emollients, and were uncertain about quantities of topical treatments to issue. Mild and moderate potency topical corticosteroids (TCS) were commonly used, but most GPs lacked confidence in recommending potent TCS, and viewed parents or carers to be fearful of using all strengths of TCS. GPs perceived adherence to treatments to be low, but provision of information to support self-care was variable. Routine review of medication use or disease control was uncommon, which GPs attributed to service constraints. Participants’ views on the causes and management of eczema were perceived to be at odds with parents and carers, who were said to be overly focused on an underlying cause, such as allergy. CONCLUSION: GP uncertainty in managing eczema, lack of routine information and review, and perceived dissonance with parents around causation and management may be contributing to low concordance with treatments.